2009
DOI: 10.1007/s11695-009-9901-z
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Glycemic Control in Morbidly Obese Type 2 Diabetic Subjects by Gastric Stimulation

Abstract: The TANTALUS system is well tolerated in obese type 2 diabetic subjects. Gastric electrical stimulation can potentially improve glucose metabolism and induce weight loss in obese diabetic patients, who are not well controlled on oral antidiabetic therapy. Further evaluation is required to determine whether this effect is due to induced weight loss and/or to direct signal dependent mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 20 publications
0
11
0
6
Order By: Relevance
“…The majority of adverse events were unrelated to the device or procedure. Most of the procedure-related events were consistent with those commonly encountered in similar laparoscopic procedures [19,20,[23][24][25][26][27].…”
Section: Prace Poglądowementioning
confidence: 56%
See 2 more Smart Citations
“…The majority of adverse events were unrelated to the device or procedure. Most of the procedure-related events were consistent with those commonly encountered in similar laparoscopic procedures [19,20,[23][24][25][26][27].…”
Section: Prace Poglądowementioning
confidence: 56%
“…Bohdjalian A et al [23] Obese patients with type 2 diabetes previously treated with oral drugs and/or insulin, BMI 33.3-49.7 kg/m 2 , (24) Implantation of pulse generator, 1 year follow-up There were 18 adverse events related to the implant procedure or the device reported in 12 subjects. All were short lived and resolved with no sequelae.…”
Section: Prace Poglądowementioning
confidence: 99%
See 1 more Smart Citation
“…Two studies, one from TANTALUS ® [39] and the other from gastric pacing [40] , found lower ghrelin levels after device activation. However, three studies, two from IGS [41,42] and another TANTALUS ® [43] study, found no statistically significant changes in ghrelin levels.…”
Section: Co-morbiditiesmentioning
confidence: 99%
“…Only one study [28,39] reported significant weight loss at both 6 and 12 mo. However, 6-mo weight loss was greater than that achieved at a later time period.…”
Section: General Considerations On Studies and Outcomes Of The Most Rmentioning
confidence: 99%